2022
DOI: 10.3389/fcimb.2022.892401
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gut Microbiota Signature and Microbe-Disease Progression Associations in Locally Advanced Non-Small Cell Lung Cancer Patients Treated With Concurrent Chemoradiotherapy

Abstract: PurposeTo evaluate the association of gut microbiome signature and disease progression in locally advanced non-small cell lung cancer (LA-NSCLC) patients treated with concurrent chemoradiotherapy (CCRT) by fecal metagenome analysis.MethodsMetagenome-wide association studies on baseline fecal samples from 18 LA-NSCLC patients before CCRT and 13 controls from healthy first-degree relatives were performed. Among the 18 LA-NSCLC patients, six patients were defined as the long progression-free survival (long-PFS) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…Our study showed a lower proportion of Firmicutes and a higher proportion of Proteobacteria and Actinobacteriota in LC patients, which is inconsistent with the results reported by Qian et al (2022) (Figure 1B). Overall, we found differences in the composition of the gut micro-biome between the LC patients and the HC group, characterized by loss of probiotics and overgrowth of potentially pathogenic bacteria.Interestingly, the ratio of Firmicutes to Bacteroidetes (FBR) has been used as an indicator of metabolism, nutrition and evaluation of gut micro-biome in cancer patients (Xi et al, 2022). Reduced FBR may be associated with the progression and recurrence of breast cancer (Okubo et al, 2020) and colorectal cancer (Gao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a lower proportion of Firmicutes and a higher proportion of Proteobacteria and Actinobacteriota in LC patients, which is inconsistent with the results reported by Qian et al (2022) (Figure 1B). Overall, we found differences in the composition of the gut micro-biome between the LC patients and the HC group, characterized by loss of probiotics and overgrowth of potentially pathogenic bacteria.Interestingly, the ratio of Firmicutes to Bacteroidetes (FBR) has been used as an indicator of metabolism, nutrition and evaluation of gut micro-biome in cancer patients (Xi et al, 2022). Reduced FBR may be associated with the progression and recurrence of breast cancer (Okubo et al, 2020) and colorectal cancer (Gao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Acidovorax and Veillonella in the sputum can help diagnose squamous cell carcinoma with 80% sensitivity, while Capnocytophaga can be used to identify lung adenocarcinoma with 72% sensitivity 22 . Regarding prognosis, both LM and GM significantly differ between groups exhibiting long and short progression‐free survival durations 69,70 . Based on the oral microbiota, the predictive potential could reach 0.89 23 .…”
Section: Discussionmentioning
confidence: 99%
“… 22 Regarding prognosis, both LM and GM significantly differ between groups exhibiting long and short progression‐free survival durations. 69 , 70 Based on the oral microbiota, the predictive potential could reach 0.89. 23 In terms of the therapeutic effects of chemotherapy or immunotherapy, numerous studies have been carried out to screen response micro biomarkers and predict clinical side effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the T group, the abundance of Proteobacteria_eggerthii was also higher than that in the M group, which was same with the result after CCRT that the abundance of Proteobacteria increased ( 66 ). After chemoradiotherapy, the Bacteroidetes abundance of individuals with short PFS was lower than that of individuals with long PFS, while the lower ratio may be associated with the progression and recurrence of colorectal cancer ( 67 ). Moreover, enrichment of Firmicutes could improve the sensitivity of ICI immunotherapy ( 68 ) and Bacteroides could enhance the anti‐CTLA‐4 therapy ( 69 ) and the anti-PD-1 immunotherapy ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Study had shown that Prevotella and 3-Oxo not only promoted the development of malignant tumors, but also reversed the anticancer effect of FOLFOX ( 73 ). Prevotella , as an important carrier of drug resistance genes, was one of the dominant bacteria in the transfer group ( 67 ).…”
Section: Discussionmentioning
confidence: 99%